2016
DOI: 10.1016/j.neulet.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin in the medial amygdala and sexual behavior in male rats

Abstract: HighlightsKisspeptin in the posterodorsal medial amygdala evokes ex-copular erections in rats.The mechanism is kisspeptin receptor specific.Kisspeptin induced GnRH and LH release are not implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
(36 reference statements)
4
42
0
Order By: Relevance
“…This included the anterior and posterior cingulate, amygdala, thalamus, and globus pallidus, which are all implicated in romantic, maternal, and unconditional love [53][54][55][56] and consistent with structures known to be involved in kisspeptin signalling in humans [19,20] and rodents [10,15,21,23,24]. Interestingly, kisspeptins enhanced activation of the amygdala in response to bonding images correlated with improved positive mood [40], a Sexual behaviours -Enhances limbic and paralimbic brain activity with correlations to reward, sexual aversion, and positive mood (H) [40] -Triggers erections (R) [51] Fear -Reduces fear responses (Z) [36][37][38]43] Social behaviours -MeA kisspeptin neurone apposition with dopaminergic and vasopressinergic neurones (R) [24] Audition -Male rodent ultrasonic vocalisations increase female ARC kisspeptin activity which correlates to the duration of female searching for male (R) [34] Mood -Antidepressant-like effects (R, H) [40,44] -Anxiolytic effects (R, Z) [31,36] -Anxiogenic effects (R) [42] Olfaction -Kisspeptin anatomical framework (R, H) [24] -Kiss1r and MeA Kiss1 roles in male olfactory partner preference (R) [30,31] -Opposite-sex urinary odours stimulate RP3V and limbic kisspeptin neurones and enhance LH surge (R) [32,33] Kisspeptin signalling potential mechanism that may contribute to the desire to bond with a partner.…”
Section: Kisspeptin and Sexual Processingmentioning
confidence: 57%
See 2 more Smart Citations
“…This included the anterior and posterior cingulate, amygdala, thalamus, and globus pallidus, which are all implicated in romantic, maternal, and unconditional love [53][54][55][56] and consistent with structures known to be involved in kisspeptin signalling in humans [19,20] and rodents [10,15,21,23,24]. Interestingly, kisspeptins enhanced activation of the amygdala in response to bonding images correlated with improved positive mood [40], a Sexual behaviours -Enhances limbic and paralimbic brain activity with correlations to reward, sexual aversion, and positive mood (H) [40] -Triggers erections (R) [51] Fear -Reduces fear responses (Z) [36][37][38]43] Social behaviours -MeA kisspeptin neurone apposition with dopaminergic and vasopressinergic neurones (R) [24] Audition -Male rodent ultrasonic vocalisations increase female ARC kisspeptin activity which correlates to the duration of female searching for male (R) [34] Mood -Antidepressant-like effects (R, H) [40,44] -Anxiolytic effects (R, Z) [31,36] -Anxiogenic effects (R) [42] Olfaction -Kisspeptin anatomical framework (R, H) [24] -Kiss1r and MeA Kiss1 roles in male olfactory partner preference (R) [30,31] -Opposite-sex urinary odours stimulate RP3V and limbic kisspeptin neurones and enhance LH surge (R) [32,33] Kisspeptin signalling potential mechanism that may contribute to the desire to bond with a partner.…”
Section: Kisspeptin and Sexual Processingmentioning
confidence: 57%
“…1). Kisspeptin signalling is required for male olfactory partner preference [30], is enhanced by opposite-sex urinary odours [32,33], modulates mate preference [31], enhances auditory-reproductive behaviour [34], dampens fear responses [36], modulates anxiety [31,36,42], has antidepressant-like effects [40,44], and triggers erections [51]. Furthermore, in healthy heterosexual men, kisspeptin enhances limbic and paralimbic brain activity specifically in response to visual-evoked sexual and romantic stimuli and these enhancements correlate with behavioural measures including sexual aversion, reward, and mood [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified MeA Kiss neurons and the POA as regulators of sexual motivation and behaviour in male rodents [15, 16, 44]. Several studies have identified various neuronal types in the POA as key players in mediating male-typical mating and paternal behaviour including neurons expressing oestrogen receptor alpha [45], progesterone receptor [46], and galanin [47].…”
Section: Discussionmentioning
confidence: 99%
“…Chemogenetic activation of MeA Kiss neurons reduces anxiety and enhances the preference for oestrous females in male mice [15]. Intra-MeA infusions of kisspeptin impact LH levels and lead to increased numbers of ex-copula erections in male rats [16], suggesting that MeA Kiss signalling regulates GnRH release and participates in sexual arousal. However, Kiss1r expression has not been identified in MeA Kiss neurons, therefore it remains unclear whether MeA Kiss neurons directly regulate these responses or whether another neuronal population is involved.…”
Section: Introductionmentioning
confidence: 99%